Discovery of novel substituted (Z)-N′-hydroxy-3-(3-phenylureido)benzimidamide derivatives as multifunctional molecules targeting pathological hallmarks of Alzheimer's disease - Shankar G.; Praveen Kumar C.; Yadav M.; Ghosh A.; Panda S.R.; Banerjee A.; Tiwari A.; Rai S.; Kumar S.; Garg P.; Naidu V.G.M.; Kulkarni O.; Modi G. (My University, 2025)
Alzheimer's disease (AD) is a neurodegenerative disorder marked by significant loss of central cholinergic neurons. This progressive deterioration leads to cognitive dysfunction and impaired motor activity, culminating in the brain cell's death at the later stages of the disease. The approved drugs for AD are limited to providing symptomatic relief for an initial period due to the multifaceted etiology of the disease. Several studies have demonstrated that rivastigmine (RIV) is a selectively potent inhibitor of butyrylcholinesterase and devoid of antioxidant, Aβ, and tau protein aggregation inhibition and anti-inflammatory properties. Therefore, to address these issues associated with RIV, novel rivastigmine-based molecules were rationally designed, synthesized, and evaluated in various in-vitro and in-vivo AD models. In in-vitro acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) inhibition studies revealed that 3q & 6e as promising leads (AChE, IC50 1.72 ± 0.15, 0.91 ± 0.016 μM, BChE, IC50 6.69 ± 0.28 μM, 1.19 ± 0.026 μM, for 3q & 6e, respectively). The computational studies (molecular docking and dynamics) further corroborated the in-vitro studies. Further, 3q and 6e were found to be potent antioxidants in the DPPH assay (IC50 16.15 ± 1.05 & 15.17 ± 0.07 μM, for 3q & 6e, respectively). Interestingly, 3q, and 6e could effectively inhibit self-induced full-length tau and Aβ1-42 aggregation. Treatment with 3q & 6e inhibited microglial activation by attenuating ROS release and mitochondrial damage. Further, 3q & 6e also suppressed NLRP3 inflammasome and NF-κB expression levels in microglial cells and halted the release of pro-inflammatory cytokines in human microglial cells. Finally, 3q & 6e were found to be efficacious in reversing the scopolamine-induced memory impairment in the Morris water maze test. The expression of various neuroprotection markers, such as BDNF and TRKB, was significantly overexpressed compared to the disease control group. © 2024 Elsevier Masson SAS